سلوك الهطل المطري في حوض نهر الكبير الشمالي - عمار, غطفان; عبد الرحمن, عباس; هيفا, مجد (Latakia University Journal -Engineering Sciences Series, 2019)
يقع حوض نهر الكبير الشمالي شمال الساحل السوري بين خطي طول ﹰ40 ﹶ45 º35, و ﹰ05 ﹶ15 º36 شرق خط غرينتش, وخطي عرض ﹰ30 ﹶ28 º35 , و ﹰ00 ﹶ59 º35 شمال خط الاستواء, تبلغ مساحته حوالي 1100 كم², وتتراوح الارتفاعات الطبوغرافية في منطقة الدراسة من 0 إلى 1700. تهدف الدراسة إلى تحديد الهطل المطري الأعظمي المستخدم في حساب الغزارات التصميمية الناجمة عن العواصف المطرية, من أجل ذلك تم تحليل معطيات الهطل المطري الساعي لثماني محطات رصد جوي، موزعة على كامل مساحة الحوض الساكب للنهر. وامتدت فترة المراقبة فيها لمدة ستة أعوام, ودُرس سلوك الهطل المطري لحوالي 50 عاصفة مطرية في كل محطة, استمرت فترة هطولها من 3 ساعات إلى 36 ساعة, و صُمِّم منحني لا بعدي للعلاقة بين الهطل والزمن. توصلت الدراسة إلى أن الكمية الأعظم للهطل في المنحني التصميمي لمختلف المحطات المدروسة تهطل في منتصف العاصفة المطرية أي في الفترة بين 45%-55% من مدة الهطل الكلية إذ إن حوالي 70% من كمية الهطل تحدث خلال 10% من مدة الهطل الكلية, ولدى مقارنة المنحني التصميمي مع منحنيات SCS (Soil Conservation Service) وجدنا أن المنحني(II) هو الأقرب للتطبيق في منطقة الدراسة. ويوصى في هذه الدراسة بالحصول على معطيات هطل مطري بمدد تقل عن ساعة، من خلال إنشاء محطات آلية تقيس الهطل خلال بضع دقائق خاصةً أن أهم ما يميز الهطل في منطقة الدراسة هو شدته, وقصر مدته. The research area presents the natural boundaries of the Al-Kabeer Al-Shamali basin. They are between 35 28' 30" , 35 59' 00" latitude in the north, and 35 45' 40", 36 15' 5" longitude in the east of Grenache. The area of the studying basin is about 1100 km² and the topographic elevations is between 0 to1700 m. The study aim is to estimate a maximum precipitation that can be used to calculate peak flow, for that a 6-year hourly rainfall data recorded in eight rain gauges was analyzed. These rain gauges are distributed on all basin area, behavior of rainfall for about 50 rainfall storms in each gage was studied, the time of these storms was between [ 3 to 36] hour, and the non unit (precipitation – time) curve has designed, this study reached to that the maximum precipitation happens in the middle of designed storm between (45-55)% of the time of storm, where 70% of precipitation happens during 10% of time of designed storm. By comparing (precipitation – time) curve with SCS curves we found that SCS 24-hr Type II is the nearest for application in the area of study, in this study it is recommended to got rainfall data in intervals less than one hour by setting digital rainfall gauges that measure rainfall volume during some minutes, and what is special about the rainfall in the area of study is (shortness, and strength).